Learning and educating with ecological ink: a tutorial teaching practice in the Serra do Espinhaço (International Journal of Geoscience, Engineering and Technology, 2020)
The present work is an extension project developed by the Tutorial Education Program (PET) - Strategies to reduce the retention and dropout of academics at UFVJM. This project aimed to develop and teach the lay population in the Diamantina region to produce ecological, inexpensive and efficient paints, from the sieved soil under dilution with water and PVA - Polyvinyl Acetate glue, in order to use them to paint facades of houses and buildings of poor families or communities present in the locality. Therefore, for the performance of the project, volunteer students were selected who had an academic performance coefficient (CRA) of less than 60 or with one or more failures in subjects, in order to meet the purposes of this PET group, combating retention and evasion. During the project, the volunteer team was monitored for the performance of CRA, trained in the production of paints and in the promotion of workshops in educational institutions, which brought up issues inherent to environmental education and the production and viability of ecological paints. The project contributed to the exchange of experiences and bonds between the external and academic community, through technical visits and offered workshops.